Lean Manufacturing in Libyan Industrial Enterprises: A Critical Review of Challenges, Opportunities, and a Contextual Implementation Framework - Mohamed Ramadan Al-Hamrouni (African Journal of Advanced Pure and Applied Sciences, 2025)
In light of increasing industrial competition and global transformations, adopting advanced production systems has become vital to enhancing the competitiveness of industrial enterprises. This paper presents a semi-systematic critical review of the published literature on the application of lean manufacturing in Libyan industrial enterprises during the period from 2010 to 2023. The findings reveal that practical application remains limited and sporadic, facing multi-level managerial, organizational, technical, and cultural challenges. Key obstacles include weak senior management commitment, a lack of specialized training, inadequate support infrastructure, and resistance to change by traditional organizational culture. The paper proposes a four-pronged implementation framework based on: strategic leadership, capacity building, contextual adaptation, and performance measurement. It also offers practical recommendations for industry practitioners, researchers, and policymakers to enable the systematic and sustainable adoption of lean manufacturing in Libya, emphasizing local specificities and drawing on international experiences in the context of reconstruction and industrial development.